KNOWLEDGE CREATION PROCESS IN THE FIRST LEVEL OF RESEARCHER FUNCTIONAL TRAINING, 7 TH ROUND IN 2010 - Purnama Alamsyah (Widyariset, 2011)
First Level of Researcher Functional Training is an attempt to improve knowledge mastery of researcher/researcher candidates. the of training program is expected to increase the researchers in the field of research in accordance with a growing need in the community. This study tried to explore the knowledge creation in the implementation of First Level of Researcher Functional Training at 7round in 2010 through analysis of Nonaka’s SECI model (Socialization, Externalization, Combination, Internalization). This study concludes with a discussion of the implementation of knowledge creation, and further development of knowledge creation in First Level ofResearcher Functional Training